AN AIDS PATIENT WITH MULTIPLE OPPORTUNISTIC INFECTIONS - Mahmud, Talha (Journal of Ayub Medical College Abbottabad, 2010)
A patient was diagnosed having advanced acquired immunodeficiency syndrome (AIDS) who suffered from various pulmonary and extrapulmonary infective complications. A number of opportunistic infections were diagnosed and prompt treatment was initiated. Due to his low CD4+ lymphocyte count that carries a higher morbidity and mortality, he experienced clinical worsening even with treatment and could not survive through this Black Death. Keywords: Human immunodeficiency virus (HIV), Pulmonary, Complications, Opportunistic infections, Acquired immunodeficiency syndrome (AIDS)